Antiamoebic Properties of Metabolites against Naegleria fowleri and Balamuthia mandrillaris - Ruqaiyyah Siddiqui; Anania Boghossian; Bushra Khatoon; Muhammad Kawish; Ahmad M. Alharbi; Muhammad Raza Shah; Hasan Alfahemi; Naveed Ahmed Khan (MDPI AG, 2022)
Naegleria fowleri and Balamuthia mandrillaris are free-living, opportunistic protists, distributed widely in the environment. They are responsible for primary amoebic meningoencephalitis (PAM) and granulomatous amoebic encephalitis (GAE), the fatal central nervous infections with mortality rates exceeding 90%. With the rise of global warming and water shortages resulting in water storage in tanks (where these amoebae may reside), the risk of infection is increasing. Currently, as a result of a lack of awareness, many cases may be misdiagnosed. Furthermore, the high mortality rate indicates the lack of effective drugs available. In this study, secondary metabolites from the plants Rinorea vaundensis and Salvia triloba were tested for their anti-amoebic properties against N. fowleri and B. mandrillaris. Three of the nine compounds showed potent and significant anti-amoebic activities against both N. fowleri and B. mandrillaris: ursolic acid, betulinic acid, and betulin. Additionally, all compounds depicted limited or minimal toxicity to human cells and were capable of reducing amoeba-mediated host cell death. Moreover, the minimum inhibitory concentration required to inhibit 50% of amoebae growth, the half-maximal effective concentration, and the maximum non-toxic dose against human cells of the compounds were determined. These effective plant-derived compounds should be utilized as potential therapies against infections due to free-living amoebae, but future research is needed to realize these expectations.